Declining number of books borrowing at an academic library in Johor - Hasan, Nur Azleen; Abdullah, Mawar Noor; Mohd Hanafi, Noor Hasanah (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA, 2020)
Libraries, regardless of their types of libraries either academic libraries, special libraries, public libraries and even in school libraries are facing a major challenge in the 21st century: for a number of years there has been a decline in the number of books being borrowed. In the academic libraries, where the library is the heart of the institution, making a clear assumption on the borrowing and loan activities must statistically being proven. This study determines the reasons of the decreasing number of borrowing books among the students; the frequency of students visit and borrow books from the library; the purpose of the students come to the library; and the types of sources that were used. This study also focuses on identifying the reasons why students reluctant to borrow books in an academic library. The significance of the study is to improve borrowing books activity in the library and thus help in promoting new books on shelves; encourage librarians in guiding users to search appropriate books in order to fulfil their needs; help library in making acquisition and circulation decisions based on the current findings and help library management in measuring their Return on Investment (ROI) as library has spent a lot on books purchase. Questionnaires were distributed to 400 random targeted respondents who experience using the library services. The insights of this study could assist the library management in measuring and evaluating their collections and improve their services to the user in future.